INFLUENCE OF PRUNING THE LEAVES TO THE PRODUCTION OF CORN PLANTS (Zea mays L.) - Kelvin Dolot; Selvie Tumbelaka (Sam Ratulangi University, 2021)
Corn plants (Zea mays L.) is a plant cereals important in the world. Maize ranks third after rice and wheat, while in Indonesian, corn ranks second after rice. Corn contains nutrients which are very high, especially carbohydrates contained in the seeds of corn exceeds the carbohydrates that exist in rice. Demand for corn increases from year to year, while the increase in production is not as fast as the surge needs. Corn production in Indonesian is not stable, many factors that influence it, among others, the varieties used, pests and diseases, and the cultivation technique is not adequate. The energy of sunlight absorbed the leaves of the plant is proportional to the leaf area that receives sunlightKeywords: pruning; corn.AbstrakJagung (Zea mays L.) merupakan tumbuhan serealia penting di dunia. Jagung menempati urutan ketiga setelah padi dan gandum, sedangkan di Indonesia jagung menempati urutan kedua setelah padi. Jagung mengandung zat gizi yang sangat tinggi, terutama karbohidrat yang terkandung di dalam biji jagung melebihi karbohidrat yang ada dalam padi. Permintaan jagung dari tahun ke tahun meningkat, sedangkan kenaikan produksi tidak secepat lonjakan kebutuhan. Produksi jagung di Indonesia tidak stabil, banyak faktor yang mempengaruhinya antara lain, varietas yang digunakan, hama dan penyakit, dan teknik budidaya yang belum memadai. Teknik pemangkasan efektif untuk meningkatkan produksi. Energi sinar matahari yag diserap daun tanaman proporsional terhadap luas daun yang menerima sinar matahari.Â Kata kunci: Â pemangkasan; Â jagung.